Settling Madagascar: when did people first colonise the world's largest island? - Mitchell, P (Taylor and Francis, 2019)
Madagascar poses a significant challenge for understanding how people colonized islands. While its inhabitants also share an African ancestry, language, genetics, and culture all point to the arrival on the island of Austronesian-speaking settlers from the far side of the Indian Ocean. Recent decades have seen increasing acceptance of a late first-millennium BC date for Madagascar’s initial settlement, based principally on arguments relating to the purported antiquity and presence of cut-marked animal bones and the pollen of humanly introduced Cannabis plants. More recently, these claims have been pushed much further back in time by the discovery of stone tools at Lakaton’i Anja and cut-marked bones at Christmas River and Lamboharana. Such arguments must be based on firm foundations if they are to be accepted. This paper evaluates them against criteria developed for assessing the timing and credibility of claims of pre-Clovis settlement in the Americas and early Polynesian presence in Remote Oceania. It concludes that they do not meet them and that for now there is thus no convincing evidence that Madagascar was settled before the mid-first millennium AD. Colonization around that time fits much better with broader patterns of contact, trade, and settlement in the wider Indian Ocean world, including other islands off Africa’s eastern coast.